2020
DOI: 10.1038/s41419-020-02857-4
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-377-3p released by mesenchymal stem cell exosomes ameliorates lipopolysaccharide-induced acute lung injury by targeting RPTOR to induce autophagy

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are the severe lung damage and respiratory failure without effective therapy. However, there was a lack of understanding of the mechanism by which exosomes regulate autophagy during ALI/ARDS. Here, we found lipopolysaccharide (LPS) significantly increased inflammatory factors, administration of exosomes released by human umbilical cord mesenchymal stem cells (hucMSCs) successfully improved lung morphometry. Further studies showed that miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…Our previous researches provided reliable results on the bene cial effects of MSCs on improving liver ischemia/reperfusion injury (IRI) in vivo and in vitro [10,11]. In addition, our and other several studies have also shown that MSCs could alleviate lipopolysaccharide (LPS)-induced ALI via their well-de ned roles in immunomodulation and differentiation into multiple different cell types, including adipocytes, osteoblasts and lung-related cell types [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 86%
“…Our previous researches provided reliable results on the bene cial effects of MSCs on improving liver ischemia/reperfusion injury (IRI) in vivo and in vitro [10,11]. In addition, our and other several studies have also shown that MSCs could alleviate lipopolysaccharide (LPS)-induced ALI via their well-de ned roles in immunomodulation and differentiation into multiple different cell types, including adipocytes, osteoblasts and lung-related cell types [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 86%
“…This is followed by an increase in inflammatory cytokines (TNF-α and IL-6), natural killer (NK) cells, Mɸ polarization, edema, and lung perfusion, eventually activating fibroblasts and myofibroblast differentiation to fibrosis in the irradiated lung ( Kabarriti et al, 2020 ). MSCs derived from the umbilical cord ( Wei et al, 2020 ), bone marrow ( Lee et al, 2012 ), and adipose tissue ( Dong et al, 2015 ) were reported to be attenuating various models of lung injury.…”
Section: Mesenchymal Stromal/stem Cell-evsmentioning
confidence: 99%
“…Similar function was noted between CDKN1B and PTEN. On the other hand, more mRNAs can be targeted by miR-377 [42,43]. Zhou W et al found NR6A1 was targeted by miR-377 in gastric cancer [43], and miR-377 could alleviate myocardial injury induced by Hypoxia/Reoxygenation via downregulating LILRB2 expression [31].…”
Section: Plos Onementioning
confidence: 99%